The predictive ability of cultural intelligence and character orientations for psychological adaptation in expatriates - Al-Krenawi , Alean; Natsheh, Numan Khaled; Al-Ja'afreh, Somaya Abdel-Hameed; Abudoush, Ahmad Nabeel; Al-Habies , Feras Ali; Khawaldeh , Omar Abdallah (Journal of International Students, 2025)
This study investigated the predictive relationships between cultural intelligence (CQ), personal orientation, and psychological adaptation among 193 expatriate students at the University of Jordan. The results revealed a significant positive correlation between CQ, personal orientation, and psychological adaptation. Regression analysis indicated that motivational CQ was the strongest predictor of psychological adaptation (62.5%), with a 73.2% prediction combined with metacognitive CQ. Productive personal orientation also demonstrated a significant predictive relationship with adaptation (52.1%). Interestingly, the cognitive dimension of CQ exhibited lower predictive power than the motivational and metacognitive dimensions, suggesting the importance of action-oriented and reflective capacities over purely knowledge-based components. Additionally, gender differences emerged, with females showing higher levels of CQ and psychological adaptation. While CQ and personal orientation both influence adaptation, their independence from one another suggests distinct pathways.